Analysis of the Influence Digital Marketing and Ease of Payment Using Qris on SMEs in Cibiru District - Rohiman, Rohiman; Apriadi, Deri (CNPLUS Publisher, 2025)
Digital marketing has revolutionized the way businesses operate, influencing consumer behavior, corporate structure, marketing approaches, and competitive capacity. It has also significantly affected the way information is accessed and interactions are determined, leading to the birth of new marketing technologies. This study uses a qualitative descriptive approach to explore the impact of digital marketing strategies and the use of QRIS among MSMEs in Cibiru District. The findings suggest that digital marketing significantly influences consumer purchasing behavior and business accessibility. Furthermore, the adoption of QRIS as a digital payment system has enhanced transaction convenience and operational efficiency for MSME actors.. The rapid development of technology, not far from everything related to the internet and the digital world, with the existence of a digital marketing strategy applied to a business allows interest to arise in people's purchasing behavior. What was initially unknown, with this digital technology a business can be accessed and conveyed to potential customers through cyberspace. The majority of business actors (around 84.6) stated that they agreed/strongly agreed that social media is used to promote products by MSME actors in Cibiru. This shows that the use of social media is quite acceptable and considered useful by micro business actors in the